Pengembangan Sistem Informasi Transaksi Penjualan Dan Komisi Agen Berbasis Web (Studi Pada PT Akademi Pembicara Indonesia) - Dony Febrian Syahputra; Satrio Agung Wicaksono; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
PT Akademi Pembicara Indonesia is an engaged company in public speaking training. The company makes a training event, then the event ticket will be sold by the agency owned by the company. The company has a problem about the agent that sells ticket but have a different price according to the price at the time of sale, a report done by agents when they get customers is often get delayed, the distribution of commissions to the agents still has errors, financial reports requires about 3 hours working time. This problem is less efficient and can harm the company. Based on the problems described earlier, a solution can be given to develop a sales transaction information system and agent commission. In the development of information systems the author using the Waterfall software development model. Waterfall is chosen because the requirements are ready and minimum change of requirements.This development method includes needs analysis, design, implementation, and testing, the process runs sequentially. At the needs analysis stage a business process modeling is conducted based on the results of interviews with stakeholders and problem analysis. The results of the needs analysis are visualized in the use case diagram and activity diagram. The results of system design produce sequence diagrams, class diagrams, relational data models, pseudocode algorithms, user interfaces. The implementation of this information system used object oriented programming for web application. The information system testing phase is done with compatibility testing, validation testing and user acceptance testing. The results on sales transaction information system and agent commission, system can run well and can be accepted by the user.